The study of Rh(iii) hydroxocomplexes using capillary zone electrophoresis with a UV–Vis detector: the development of the method. Issue 33 (6th August 2019) - Volchek, Victoria V.; Shuvaeva, Olga V.; Berdyugin, Semen N.; Vasilchenko, Danila B.; Korenev, Sergey V.
Abstract : Capillary zone electrophoresis was firstly employed to study a mixture of rhodium(iii ) polynuclear hydroxocomplexes. Abstract : The expediency of capillary zone electrophoresis application in the study of a mixture of rhodium(iii ) hydroxocomplexes is shown for the species formed during the thermal treatment of [Rh(OH)6 ] 3− at 60 °C in alkaline media. As these compounds are unstable in solution because of polycondensation at pH > 10 and the formation of insoluble rhodium(iii ) hydroxides at pH 5–10, their acidic derivatives with terminal aqua ligands acted as the objects of the study. Optimal separation conditions were achieved using sodium perchlorate as a background electrolyte, a voltage of +20 kV and pH 2.6. Rhodium(iii ) species with different nuclearities were identified in accordance with their UV spectra and the regularities of electrophoretic migration in the capillary. The presence of a dimer was also verified by the spiking of the mixture under investigation with a previously synthesised complex [Rh2 (μ-OH)2 (H2 O)8 ](NO3 )4, which confirms the correct identification.